2022
DOI: 10.3390/app12188941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lead, Copper and Cadmium on Bioaccumulation and Translocation Factors and Biosynthesis of Photosynthetic Pigments in Vicia faba L. (Broad Beans) at Different Stages of Growth

Abstract: Trace elements in the environmental media contribute to toxicities of different types. Their presence in the arable pedosphere is a human-health risk factor. This study focused on Vicia faba represented by two Tunisian varieties of bean (Mamdouh) and faba bean (Badii). The objective was to analyze the effects of lead, copper and cadmium on their growth, chlorophyll-content and carotenoids-content, as well as the bioaccumulation and translocation factor, at different stages of growth. For each metal, the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Due to the complex dynamic interaction among heavy metals, soil, and organisms, only some of the heavy metals in the soil can be bio-absorbed and assimilated [21]. The migration and transformation of heavy metals in the soil varied with the available state or occurrence form [22], and their biological effectiveness on plants also differed [23]. However, previous research on heavy metals in soil mostly focused on the total content level, which do not accurately reflect the actual ecological risk of heavy metals pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex dynamic interaction among heavy metals, soil, and organisms, only some of the heavy metals in the soil can be bio-absorbed and assimilated [21]. The migration and transformation of heavy metals in the soil varied with the available state or occurrence form [22], and their biological effectiveness on plants also differed [23]. However, previous research on heavy metals in soil mostly focused on the total content level, which do not accurately reflect the actual ecological risk of heavy metals pollution.…”
Section: Introductionmentioning
confidence: 99%
“…syl-vestris 44 , 45 and contrary to the results obtained by Brun et al 46 as regards the Cu accumulation in aerial parts in the case of maise . Another study in which high values of Cu were identified in two Tunisian varieties of bean (Mamdouh) and faba bean (Badii) suggested that Cu is readily translocated to the aerial parts of the plants, owing to its role in plant metabolism because after all, it is a necessary micronutrient 47 . Moreover, the high bioavailability of Cu is possibly due to its high solubility under acidic conditions as free water ions as reported in the case of Cd 48 .…”
Section: Discussionmentioning
confidence: 99%